2x+8(x+3) = 3(x-13) please show the work, i’ll mark brainliest

Question

2x+8(x+3) = 3(x-13)

please show the work, i’ll mark brainliest

in progress 0
Hồng Cúc 1 year 2021-09-05T01:44:28+00:00 2 Answers 9 views 0

Answers ( )

    0
    2021-09-05T01:45:32+00:00

    Answer:

    x = -9

    Step-by-step explanation:

    2x + 8( x + 3 ) = 3( x – 13 )

    Dstribute;

    2x + 8 ( x + 3 ) = 3 ( x – 13 )

    2x + ((8)(x)) + ((8)(3)) = ((3)(x)) – ((13)(3))

    2x + 8x + 24 = 3x – 39

    Combine like terms;

    2x + 8x + 24 = 3x – 39

    10x + 24 = 3x – 39

    Inverse operations;

    10x + 24 = 3x – 39

    -3x            -3x

    7x + 24 = -39

         -24     -24

    7x = – 63

    /7       /7

    x = -9

    0
    2021-09-05T01:46:14+00:00

    first distribute 8 and 3 through parenthesis. this makes the equation
    2x+8x+24=3x-39

    collect like terms, such as “2x+8x” this becomes 10x. plug in 10x.

    10x+24=3x-39. now move variable and constant. 10x-3x=-39-24
    collect like terms again. 10x-3x becomes 7x.

    7x=-39-24.
    -39-24=-63

    7x=-63 divide both sides by 7.

    x=-9

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )